Parasomnias: Common sleep disorders in children suffering from obstructive sleep apnea syndrome - Alexander Torres Molina (Medisur)
The sleep disorders have a tendency to chronic evolution in approximately the 30% of children and adolescents, what constitute the main parasomnias clinical expressions of these phenomena. The Obstructive Sleep Apnea Syndrome constitute a high prevailment ailment which affects the 2% of the childish population approximately it is considered an entity because of its cognitive and somatic resounding. Parasomnias are part of the complex symptomatic night cortege observed in OSAS, stablishing a direct physiopathology relationship between both of them. The reduction of the apnea episodes after the adenotonsillar hyperplasia surgical treatment is accompanied by diminishing of the sleep disorders modification in this patient.